2014
DOI: 10.5194/acp-14-11633-2014
|View full text |Cite
|
Sign up to set email alerts
|

Observations of rapid aerosol optical depth enhancements in the vicinity of polluted cumulus clouds

Abstract: Abstract. During the July 2011 Deriving Information on Surface conditions from Column and Vertically Resolved Observations Relevant to Air Quality (DISCOVER-AQ) field experiment in Maryland, significant enhancements in Aerosol Robotic Network (AERONET) sun-sky radiometer measured aerosol optical depth (AOD) were observed in the immediate vicinity of non-precipitating cumulus clouds on some days. Both measured Ångström exponents and aerosol size distribution retrievals made before, during and after cumulus deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 90 publications
(107 reference statements)
6
65
0
Order By: Relevance
“…In addition to the well-known process of hygroscopic particle growth, there is a mechanism of the gas-to-particle conversion that occurs more intensively in the aqueous phase in cloud droplets due to the oxidation of gases (SO 2 , NO x , SOA) (Eck et al, 2014). Due to this mechanism in the presence of convective cloudiness the formation of new aerosol particles may observe providing higher aerosol loading during the periods with higher cloud amount in the vicinity of clouds (Eck et al, 2014).…”
Section: Data Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the well-known process of hygroscopic particle growth, there is a mechanism of the gas-to-particle conversion that occurs more intensively in the aqueous phase in cloud droplets due to the oxidation of gases (SO 2 , NO x , SOA) (Eck et al, 2014). Due to this mechanism in the presence of convective cloudiness the formation of new aerosol particles may observe providing higher aerosol loading during the periods with higher cloud amount in the vicinity of clouds (Eck et al, 2014).…”
Section: Data Descriptionmentioning
confidence: 99%
“…However, several recent studies indicated that clouds can have a real impact on AOT. These mechanisms of aerosolcloud interaction include aerosol hygroscopic growth, increasing aerosol concentration due to air convergence, and new particles formation in the presence of clouds (Su et al, 2008;Jeong and Li, 2010;Eck et al, 2012Eck et al, , 2014. In addition to the well-known process of hygroscopic particle growth, there is a mechanism of the gas-to-particle conversion that occurs more intensively in the aqueous phase in cloud droplets due to the oxidation of gases (SO 2 , NO x , SOA) (Eck et al, 2014).…”
Section: Data Descriptionmentioning
confidence: 99%
See 3 more Smart Citations